PENGARUH PERPUTARAN PERSEDIAAN DAN MODAL KERJA TERHADAP PROFITABILITAS “STUDI KASUS PT UNILEVER TBK DI BURSA EFEK INDONESIA (2019-2023)”: Indonesia - Ratri; Rezki Fani; Musmulyadi; Fahmiah Akilah (LPPM STIEM BONGAYA, 2025)
This study aims to analyze the impact of inventory turnover and working capital turnover on profitability, specifically Return on Assets (ROA) at PT Unilever Tbk listed on the Indonesia Stock Exchange from 2019 to 2023. The research uses a quantitative approach with secondary data obtained from financial statements published by PT Unilever Tbk. Multiple regression analysis was used to test the hypotheses. The results show that inventory turnover and working capital turnover have no significant effect on ROA. These findings suggest that, although theoretically both inventory turnover and working capital turnover should influence profitability, external factors such as marketing strategies, market competition, and macroeconomic conditions play a more significant role in determining profitability